Simultaneous production of hydrogen and carbon nanotubes from biogas: On the design of combined process - Rattanaamonkulchai, Raminda; Kludpantanapan, Thunyathon; Nantapong, Paveenuch; Srifa, Atthapon; Koo-Amornpattana, Wanida; Chaiwat, Weerawut; Sakdaronnarong, Chularat; Kiatphuengporn, Sirapassorn; Charinpanitkul, Tawatchai; Assabumrungrat, Suttichai; Wongsakulphasatch, Suwimol; Eiad-ua, Apiluck; et al. (My University, 2022)
We introduced a novel combined process of CO2 methanation (METH) and catalytic decomposition of methane (CDM) for simultaneous production of hydrogen (H2) and carbon nanotubes (CNTs) from biogas. In this process, biogas is catalytically upgraded into CH4-rich gas in METH reactor using Ni/CeO2 catalyst, and the obtained CH4-rich gas is subsequently decomposed into H2 and CNTs in CDM reactor over CoMo/MgO catalyst. Among the three different process scenarios proposed, the combined process with a steam condenser equipped between METH and CDM reactors could greatly improve a CNTs productivity. The CNTs production yield increased by more than 2.5-fold, maximizing at 9.08 gCNTs/gCat with a CNTs purity of 90%. The deposited carbon product was characterized as multi-walled carbon nanotubes (MWCNTs) with a surface area of 136.0 m2/g, comparable with commercial CNTs of 199.8 m2/g. The remarkable IG/ID ratio of 2.18 confirms a superior portion of graphitic carbon in the synthesized CNTs upon the commercial CNTs with IG/ID = 0.74. Notably, the CH4 conversion reached 94.5%, while the CO2 conversion achieved 100%, resulting in the H2 yield and H2 purity higher than 90%. This combined process demonstrates a promising route for production of high quality CNTs and high purity H2 with complete CO2 conversion using biogas as abundant renewable energy resources. In addition, the test of raw biogas showed no deactivation of catalyst, justifying the implementation of the developed process for real biogas without purification.
Keywords: Biogas; Carbon nanotubes; Catalytic decomposition of methane; CO2 methanation; Combined process; Hydrogen